Maternal urinary levels of PAH metabolites, umbilical cord blood telomere length and anthropometric indices in newborns - Xiang Li; Xiaofeng Yu; Xin Lian; Longdan Kang; Lei Yang; Fang Ba (Ecotoxicology and Environmental Safety)
The existing evidence indicating that prenatal exposure to polycyclic aromatic hydrocarbons (PAHs) is associated with a range of adverse outcomes, including alterations in anthropometric indices, underscores the need for further investigation into the underlying mechanisms. This study aims to examine the effects of prenatal PAH exposure on anthropometric indices and telomere length (TL), as well as to explore whether changes in TL can serve as a predictor of alterations in anthropometric measures. The study was conducted in Shenyang, China, with 2460 pregnant women participating between 2022 and 2023. Maternal urine samples were analyzed for eleven PAH metabolites, and neonatal outcomes, such as birth weight (BW), birth length (BL), and head circumference (HC), were extracted from medical records as anthropometric indices. We employed multiple linear regression (MLR), generalized quantile g-computation (g-comp), Bayesian Kernel Machine Regression (BKMR), and mediation analysis to comprehensively assess the associations between PAH exposure and umbilical TL and neonatal outcomes. Notably, significant negative associations were found between several PAH metabolites and umbilical telomere length (TL). These metabolites included 2-hydroxy naphthalene (2-OH Nap), 1-hydroxy pyrene (1-OH Pyr), 6-hydroxy chrysene (6-OH Chr), 9-hydroxy benzo(a)pyrene (9-OH Bap), and the sum of hydroxylated PAHs (Σ-OH PAHs). Additionally, negative correlations were identified between specific PAH metabolites and HC, although no significant associations were found for BW. Birth weight showed a significant inverse relationship with metabolites such as 1-hydroxy phenanthrene (1-OH Phe), 9-hydroxy phenanthrene (9-OH Phe), and 1-hydroxy naphthalene(1-OH Nap). Results from g-comp analysis and BKMR indicated significant mixture effects of PAHs on umbilical TL and HC, with more heterogeneous effects on BW and BL. Mediation analysis indicated that alterations in umbilical TL partially mediated the associations between PAH exposure and BW and HC. Notably, metabolites such as 2-OH Nap and the Σ-OH PAHs demonstrated substantial mediation effects. Overall, our findings suggest that changes in umbilical TL partially mediate the associations between prenatal PAH exposure and HC and BW, highlighting the complex pathways through which PAH metabolites may influence neonatal development.